2016
DOI: 10.4081/monaldi.2006.567
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary complications in primary hypogammaglobulinemia: a survey by high resolution CT scan

Abstract: It seems that the majority of hypogammaglobulinaemic patients suffer from the mild type of bronchiectasis, which is mostly observed in the proximal bronchi of the lower lobe segments. The delay of diagnosis plays an important role in the occurrence of this complication in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…A reduced rate of carbon monoxide uptake and restrictive ventilatory pattern is typically found in CVID patients with ILD (63). A significant correlation between the HRCT score and the predicted values in pulmonary function test has been confirmed in several studies (46), while the others did not find such associations (49, 87). There is a negative correlation between a number of episodes of pneumonia and lung function tests.…”
Section: Respiratory Manifestations Of Primary Immunodeficienciesmentioning
confidence: 72%
See 1 more Smart Citation
“…A reduced rate of carbon monoxide uptake and restrictive ventilatory pattern is typically found in CVID patients with ILD (63). A significant correlation between the HRCT score and the predicted values in pulmonary function test has been confirmed in several studies (46), while the others did not find such associations (49, 87). There is a negative correlation between a number of episodes of pneumonia and lung function tests.…”
Section: Respiratory Manifestations Of Primary Immunodeficienciesmentioning
confidence: 72%
“…The bronchiectasis is usually in the lower or middle lobes. It seems that the majority of the hypogammaglobulinemic patients suffer from the mild type of bronchiectasis (46). Bronchiectasis and bronchial wall thickening occurs in 17–76% of antibody deficiency patients and are well recognized complication in these patients (17).…”
Section: Respiratory Manifestations Of Primary Immunodeficienciesmentioning
confidence: 99%
“…Most patients with hypogammaglobulinemia experience the mild type of bronchiectasis [67]. Patients with PADs are at a significantly increased risk for developing bronchiectasis [65,68,69], as we indicated in a study in which 37.5% of patients with bronchiectasis were diagnosed with defects in antibody-mediated immunity [70].…”
Section: Bronchiectasismentioning
confidence: 99%
“…Longitudinal data in children with bronchiectasis suggest that early diagnosis and intensive treatment slows deterioration of lung function (9,10). Gharagozlou showed that in patients with primary hypogammaglobulinemia, there had been a longer delay in diagnosis among those who developed bronchiectasis compared to those who did not (21).…”
Section: A B a B Discussionmentioning
confidence: 99%